Design and Validation of a Project-Based Learning (PjBL)-Based Science Module through Water Rocket Experiments on Motion, Force, and Pressure - Wahyuningsi, Wahyuningsi; Akhsan, Hamdi; Kistiono, Kistiono (Empiricism Journal, 2026)
This study aimed to develop and validate a Project-Based Learning (PjBL)-based science module using water rocket experiments for the topics of motion, force, and pressure in junior high school. The study employed a Research and Development (R&D) approach using the 4D model, consisting of Define, Design, Develop, and Disseminate stages. The module was designed to support meaningful science learning by integrating project activities, inquiry-based student worksheets, and hands-on experimentation. Validation was conducted by three experts, including a science education expert, a science content expert, and an experienced science teacher. The validation focused on curriculum alignment, pedagogical appropriateness, content accuracy, worksheet quality, presentation, and assessment. The results showed that the developed module was categorized as very valid, with an average validation score of 89.8%. The highest score was obtained in presentation and language aspects (92%), while curriculum alignment and assessment each obtained 90%. The findings indicate that the module is feasible for use as a science teaching material in junior high school and is pedagogically promising for supporting active learning and scientific reasoning. However, further empirical studies are needed to examine its effectiveness in improving students’ learning outcomes, motivation, and scientific literacy.